Computational and experimental studies on SnO2 thin films at various temperatures - K. Gurushankar; M. Grishina; M. Gohulkumar; K. Kannan (Компьютерная оптика, 2023)
Tin oxide (SnO2) thin films was prepared by dip-coating technique at various bath temperatures (313, 333, 353 and 373 K) and annealed at 673 K in this study. And the obtained results were studied and correlated with the computational method. Scanning electron microscopy (SEM) investigation demonstrated that the prepared samples are spherical with agglomeration. The elemental analysis (EDAX) confirms the presence of Sn and O. Further, the SnO2 thin films microstructures are simulated, their thermodynamic and surface properties have been calculated. Micro-Raman spectra were recorded for the prepared samples. Micro-Raman results exhibit the first-order Raman mode E1gsub> (475 cm−1) indicating that the grown SnO2 belongs to the rutile structure. In addition, the envelope method used for studying optical characteristics of the thin films from the transmittance spectra. The semiconducting nature of the films has been noticed from linear I-V characteristics. Furthermore, the electrical conductivity studies suggest that the highest conductivity samples acquire the lowest activation energy and their values are also in the semiconducting range.